Media frames, partisan identification and the Australian banking scandal - Culpepper, P; Lee, T (Taylor and Francis, 2021)
In 2017 the Australian government appointed a Royal Commission of inquiry into malfeasance in the banking sector. This article reports findings from a 2018 survey on attitudes to financial regulation and a survey experiment testing different media treatments. Attitudes on financial regulation are distinct from left-right positions on redistributive issues; we find no significant relationship between partisan identification and preferences for financial regulation. In the experimental treatment, all three frames catalysed anger and disgust from readers. However, neither of the two strong partisan frames moved policy preferences. The non-partisan frame – which included messages associated with both left and right, and which linked both parties to systemic capture by the banks – was the only article that had any effect on policy preferences, but only with non-partisan identifiers. Our results suggest that persuasive frames focused on the capture of politics by banking interests can move opinions of swing voters on financial regulation.